ORAL NUTRITION SUPPLEMENT (ONS) BERBASIS BAHAN PANGAN LOKAL UNTUK PASIEN MALNUTRISI RUMAH SAKIT - Fitria, Mona; Dewi, Maryati; Wulandari, Dieni (Poltekkes Kemenkes Bandung, 2024)
Hospitalized patients with malnutrition are at risk of experiencing prolonged healing processes, extended hospital stays, and a decline in quality of life. One effort to enhance energy and protein intake is through oral administration using Oral Nutrition Supplements (ONS). ONS can be developed as a liquid food formula based on local ingredients, such as tilapia fish and sweet potato. This research aimed to determine the impact of tilapia fish flour and sweet potato flour formulations on the quality of ONS, including organoleptic properties, nutritional value, physical quality, microbiology, and shelf life. The experimental design involves three formulations of tilapia fish and sweet potato flour: 80%:20% (F1), 60%:40% (F2), and 40%:60% (F3). Organoleptic properties are analyzed using hedonic tests by 30 semi-trained panelists. The results showed that ONS with the best organoleptic properties was F2, with an average hedonic score of 5.60 (overall). Kruskal-Wallis test results showed that the formulation significantly influences the taste, aroma, color, and overall of ONS. Nutritional analysis revealed that ONS F2 per 100 mL contains 112 Kcal of energy, 5.4 g of protein, 3.8 g of fat, and 14.1 g of carbohydrates. The viscosity of ONS F2 was 226.5 cP, and the osmolality was 589 mOsmol/kg H2O. ONS F2 also complied with microbiological quality standards. The shelf life of ONS F2 at 2°C was estimated to be 24 days, with an expected selling price of Rp. 23,000 per serving. The research results are expected to apply to malnourished patients in hospitals.